Role of blood cholesterol transport system disturbances in atherosclerosis development in rheumatoid arthritis - T. V. Popkova; D S Novikova; A A Novikov; E N Alexandrova; E S Mach; T N Gawa; A. V. Masova; L A Gracheva; A A Bologov; E L Nasonov (Научно-практическая ревматология)
Objective. To study role of inflammation and disturbances of blood cholesterol transport system in atherosclerotic damage development in rheumatoid arthritis (RA). Material and methods. 84 RA pts with mean age 48 years and mean disease duration 87 months were included. Control group consisted of 15 humans of comparable age and sex without rheumatic diseases. Carotid sonographic scanning was performed to reveal vascular atherosclerotic damage. Cholesterol (CL), triglycerides (TG) and high-density lipoprotein cholesterol (HDLC) serum levels were evaluated with colorimetric and photometric methods, CRP, apoAl and LP(a) levels were assessed by immunonephelometric method. Results. Dyslipidemia (DLP) frequency analysis showed differences only for LP(a). Increase of LP(a) and TG concentrations in RA was more frequent than in control. CL and HDLC levels did not differ. Intima-media complex (IMC) thickness in RA and control was the same. Atherosclerotic plaques (AP) in RA were more frequent. RA pts showed negative correlation between IMC thickness and HDLC, as well as between HDLC values, apoAl and CRP. LP(a) level correlated with DAS4. There was no association between concentrations of CL, TG, HDLC, low-density lipoprotein cholesterol (LDLC), apo В and Al, LP(a) and extra-articular RA features and glucocorticoid administration. In pts with high LP(a) level AP were more frequent, activity of RA, apo B, LDLC levels were higher than in pts with normal level of this LP. LP(a) values in pts with AP were higher than in pts without AP (p<0,05). Conclusion. Chronic inflammation in RA plays an important role in disturbances in blood cholesterol transport system. LP(a) level increase is a risk factor of atherosclerotic vascular damage.